Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPAS Menggunakan Media Ular Tangga Berbasis Digital di Kelas V SDN 101766 Bandar Setia - Sari, Wulan Tahnia; Harahap, Yulia Sari; Ningsih, Ayu Melati; Nurhafni, Nurhafni; Ritonga, Farhan Ardian (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the learning outcomes of students in Magnet material using digital-based snake and ladder media in grade V of SD Negeri 101766 Bandar Setia. The method used is Classroom Action Research (PTK) which consists of 4 stages of activities in each cycle consisting of action planning, implementation of actions, observation/data collection and finally reflection. The subjects in this study are 24 students in class V of SD Negeri 101766 Bandar Setia. The instruments used in this study are multiple-choice test questions as many as 10 questions and an assessment rubric. The data collection technique uses direct observation techniques and uses quantitative data analysis techniques. The results of the research from the implementation of two cycles, where in the pre-cycle stage obtained student learning outcomes with an average of 65.83, then carried out the first cycle obtained a learning outcome score with an average of 75.42 which increased from pre-cycle to cycle I of 9.59. Finally, conducting cycle II obtained a learning outcome score of 82.08 which increased from cycle I to cycle II of 6.66. It can be concluded that the use of digital-based snake and ladder media can improve students' social science learning outcomes